Performance, corporate governance and new regulation (Desempeno, gobierno corporativo y nueva regulacion) - García, Heriberto (Facultad de Contaduría Pública y Administración U.A.N.L., 2012)
Abstract. After the adoption of the Corporate Governance Code (Code) in Mexico, many companies increased financial performance and the leveraged during the following five years; we investigated the effect of how those firms improved the corporate governance practices and how was translated into better risk return company. We analyzed how and where better corporate governance practices affects performance and what was the relationship with Transparency, New Regulation and Governance Practices. Also we explored the gaps between transparency and information disclosure of Mexican Firms listed in U.S stock exchange and non U.S listed firms our findings were related to the potential growth of the Mexico Financial Market, Law and Finance.